The Influence of Liquidity on Bond Credit Ratings: Evidence from The Indonesian Corporate Bond Market - Firly Armanda; Buddi Wibowo (PT Mattawang Mediatama Solution, 2024)
This study examines the effectiveness of various liquidity proxies in distinguishing between Investment Grade (IG) and High Yield (HY) bonds within the Indonesian corporate bond market. Utilizing logistic regression models across a dataset of 30,738 observations for IG bonds and 176 observations for HY bonds, we evaluated the impact of six liquidity proxies: Range Measure (RG), Hui Heubel ratio (HH), Market Share (MS), Interquartile Range (IR), Imputed Roundtrip Cost (IRC), and Trading Volume (TV). The findings reveal that the Imputed Roundtrip Cost (IRC) is the most reliable indicator of liquidity, demonstrating a significant negative relationship with the likelihood of a bond being classified as IG. This suggests that higher IRC values, which represent higher transaction costs, are associated with lower liquidity. In contrast, the other proxies, including the Hui Heubel ratio, did not show consistent or significant impacts in line with the hypotheses. The study concludes that IRC is the best measure for assessing liquidity in the Indonesian corporate bond market.